Utilización de Fundas de Polietileno, Papel y Tela como medida preventiva para el Control de la Pudrición Gris (botrytis cinerea) en la Florícola Diamond Roses Joseguango Bajo – Cotopaxi, octubre 2016 – agosto 2017. - Cajas Pacheco, Diego Patricio (2017)
This project was carried out at the Diamond Roses Floriculture Farm located in the Joseguango Bajo parish, Latacunga Canton, Cotopaxi Province, located at an altitude of 2725 masl, Latitude of 00 ° 48'35.87 ”S and Longitude of 78 ° 35'40 "Or, the objective was to evaluate the use of polyethylene, paper and fabric covers as a preventive measure for the control of gray rot (Botrytis cinerea), also as objectives was to determine the best preventive treatment to control B. cinerea, identify the percentage of infection caused by B. cinerea in the two varieties of rose and perform the economic analysis. Scientific observation was the methodology used, in addition the tabulation of the recorded data was carried out with the Infostat 2016 software. Knowing that in rose bush cultivation the application of chemical products is the main alternative to eradicate pests and diseases. In the present investigation, polyethylene, paper and cloth covers were used as a control in two varieties of rose, Pink Floyd! and Polar Star, which are susceptible to the attack of Botrytis cinerea, obtaining the following results: for the percentage of incidence of B. cinerea, the treatments with the control of polyethylene covers presented the lowest values, where treatment 1 (Pink Floyd ! + Polyethylene cover) and 4 (Polar Star + polyethylene cover) with 10% and 11.67% respectively, in the comparison of controls, C1 (Polyethylene cover) obtained the lowest percentage with 10.83% in reference To the other controls, for the comparison of varieties V1 (Pink Floyd!) obtained the lowest percentage with 31.67% compared to V2 (Polar Star) with 41.67. In the variable stem length, an average of 86.07 was recorded for treatment 7 (Pink Floyd! + Conventional control), in comparison with the other treatments, being T4 (Polar Star + polyethylene cover), which registered the lowest average with 70.22. I know